2008
DOI: 10.1103/physrevb.77.205406
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities at vicinal crystal surfaces: Competition between electromigration of adatoms and kinetic memory effect

Abstract: coefficient and F is a force acting on the adatoms ( F is related to the electric current heating the crystal ). In the limit of fast surface diffusion and slow kinetics of atom attachment-detachment at the steps we formulate a model free of the quasi-static approximation in the calculation of the adatom concentration on the terraces. The linear stability analysis of a step train results in an instability condition in the formτ is the dimensionless life-time of an adatom before desorption, f and η are dimensio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In most analytical models step movement factor is neglected 8,10-15 . However as it was discussed lately particle advection is in fact comparable with electromigration or Schwoebel barrier asymmetry 10,[34][35][36] . Results of our Monte Carlo (MC) simulations show that the step bunching happens at the ideal stepped surface with Schwoebel barrier assumed to be zero and no external particle driving present.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most analytical models step movement factor is neglected 8,10-15 . However as it was discussed lately particle advection is in fact comparable with electromigration or Schwoebel barrier asymmetry 10,[34][35][36] . Results of our Monte Carlo (MC) simulations show that the step bunching happens at the ideal stepped surface with Schwoebel barrier assumed to be zero and no external particle driving present.…”
Section: Introductionmentioning
confidence: 99%
“…Surface evolution is an effect of individual particle jumps and as a result steps join together building bunches at the surface. It was shown that bunching can be caused by Schwoebel barriers 32 , diffusion at step edge 33 , impurities 28 or driven particle flow [8][9][10]34 . In most analytical models step movement factor is neglected 8,10-15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability is caused solely by the time delay that is introduced into the interaction between steps by the finite time scale of the adatom dynamics, similar to the instabilities induced in follow-the-leader models of highway traffic by the finite reaction time of drivers [52,53]. In the presence of electromigration and sublimation, the non-quasistatic model reproduces the main features of the phase transition described above in Sect.1.3.4 [68].…”
Section: Beyond the Quasistatic Approximationmentioning
confidence: 56%
“…This observation is in agreement with the results of recent numerical modeling of the step bunching process which theoretically predicted the existence of a critical electromigration force as well as the formation of step density waves with relatively weak or zero electromigration. 16,17 These new models extend beyond the quasistatic approximation of earlier models 8,9 and take into account the movement of atomic steps as well as a different rate of adatom surface diffusion, step crossing, and attachment-detachment at the steps. 16,17 However, the formation of step density waves in these simulations 16 is observed at an electromigration force which is two orders of magnitude larger than the F cr = 2.7 ϫ 10 −18 N deduced in our experiment on the assumption that effective charge q eff of a Si adatom is equal to 1/3 of the elementary electric charge.…”
mentioning
confidence: 99%